2016
DOI: 10.1007/s10029-016-1465-y
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes and costs of laparoscopic versus open inguinal hernia repair

Abstract: This study demonstrates the LOS and perioperative outcomes were superior in the LIHR group; however, the overall cost was higher due to the supplies. Advancement in technology, surgeons' skill level and preference of supplies are all factors in decreasing the overall cost of LIHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 25 publications
1
14
0
2
Order By: Relevance
“…Overall, there were more male patients and more open procedures performed, which is consistent with the literature [7]. There were significant differences in patient comorbidities between the nonsmoking and the historical smoking group which may indicate that smokers, even if remote in their history of smoking, were ''more sick'' than non-smokers and were at greater risk of complications postoperatively.…”
Section: Discussionsupporting
confidence: 79%
“…Overall, there were more male patients and more open procedures performed, which is consistent with the literature [7]. There were significant differences in patient comorbidities between the nonsmoking and the historical smoking group which may indicate that smokers, even if remote in their history of smoking, were ''more sick'' than non-smokers and were at greater risk of complications postoperatively.…”
Section: Discussionsupporting
confidence: 79%
“…A recent study comparing laparoscopic vs open surgery found that laparoscopic repair was superior to open one in terms of surgical outcome and complications. 3 , 5 Another meta-analysis found that the frequency of complications was 1.76 times higher in open repair than laparoscopic repair. 13 Our findings did not correlate to their results in terms of complications.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, its operative cost is higher than open techniques despite the overall cost favoring laparoscopic approaches in terms of postoperative outcomes. 5 Total extraperitoneal (TEP) is the most frequently preferred method among laparoscopic hernia repair techniques. Unlike other techniques, TEP does not require the intraperitoneal cavity to be entered meaning that intra-abdominal complications such as organ injury and postoperative ileus can be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…The next work may be to select a particular technique among both (open technique and laparoscopic technique) for specific hernia operation and also to find a cost-effective method. The results favored the outcomes for laparoscopic technique as compared to open mesh surgery in inguinal hernia repair, but the overall cost was higher in laparoscopic technique because of preference, advancement and surgeons’ level of skills [125]. Richards et al.…”
Section: Mesh Advancementsmentioning
confidence: 99%